Prospective Investigation on the Paternity Intention and Affecting Factors in 84 Post-treatment Testicular Cancer Patients - Yenigurbuz, Serkan; Ediz, Caner; Kizilkan, Yunus Emre; Akan, Serkan; Pehlivanoglu, Mehmet; Temel, Muhammed Cihan; Tavukcu, Hasan Huseyin; Erturk, Tuna; Yilmaz, Omer (Urology Journal, 2023)
Purpose: to investigate the factors affecting post-treatment paternity intention in patients followed up after the diagnosis of testicular cancer and to make recommendations for the early postoperative period based on the identified factors. Materials and Methods: This prospective descriptive study included total 185 patients who presented to our outpatient clinic between February 2000 and July 2020 who had radical orchiectomy due to suspected testicular cancer based on physical examination and other assessments. Contact information was found for 88 of 185 patients, and accordingly, the patients were reached by one-to-one phone calls. Upon literature review, a questionnaire consisting of 10 previously validated items was developed by the researchers. The patients were compared by separating them into two groups composed of patients with (Group 1) and without (Group 2) paternity intention. Results: A total of 84 patients participated in the study, and the participation rate was 95.5%. It was found that 19 of 32 (38%) patients with paternity intention already had children. Only 21 (40%) of 52 patients without paternity intention were married. The mean age was 26.65 (18–39) years in Group 1, while it was 28.73 (19–45) years in Group 2. Tumor volume and serum tumor markers were higher in Group 2 than in Group 1. Parameters such as testicular side in which the tumor was located, smoking status, undescended testis history, and postsurgical chemotherapy history were not statistically significant difference between the two groups. Conclusion: The major findings included that the young aged, unmarried, and serious testicular cancer (Tumor volume and serum tumor markers were higher) can be affecting factors for testicular cancer patients’ paternity intention. Early psychological counseling about paternity may be useful for testicular cancer patients.